New parameterization schemes for the continuation load flow method - Alves, D. A. [UNESP] (2000)
The conventional load flow methods are considered to be inadequate to obtain the maximum loading point (MLP) due to ill-conditioning problems at and near this critical point. As far as the Newton method is concerned, the Jacobian matrix becomes singular at MLP. Continuation methods are efficient tools for solving this kind of problem, since different parameterizations are used in order to avoid such ill-conditioning problems. In this paper new parameters are presented and tested, namely the total power losses (real and reactive), the power at the slack bus (real or reactive); and the reactive power at generation buses. The results obtained with the new approach for the IEEE test systems (14, 30, 57 and 118 buses) show that the characteristics of the conventional method are not only preserved but also improved. In addition, it is shown that the proposed method and the conventional one can be switched during the tracing of PV curves in order to efficiently determine all points with few iterations.